Approaching ancient disease from a One Health perspective: Interdisciplinary review for the investigation of zoonotic brucellosis. (4th December 2019) - Bendrey, Robin; Cassidy, Joseph P.; Fournié, Guillaume; Merrett, Deborah C.; Oakes, Rebecca H. A.; Taylor, G. Michael
Abstract: Today, brucellosis is the most common global bacterial zoonosis, bringing with it a range of significant health and economic consequences, yet it is rarely identified from the archaeological record. Detection and understanding of past zoonoses could be improved by triangulating evidence and proxies generated through different approaches. The complex socioecological systems that support zoonoses involve humans, animals, and pathogens interacting within specific environmental and cultural contexts, and as such, there is a diversity of potential datasets that can be targeted. To capture this, in this paper, we consider how to approach the study of zoonotic brucellosis in the past from a One Health perspective, one which explicitly acknowledges the health link between people, animals, and environments (both physical and cultural). One Health research is explicitly interdisciplinary and conceptually moves away from an anthropocentric approach, allowing the component parts to be considered in holistic and integrated ways to deliver more comprehensive understanding. To this end, in this paper, we review the methods, selected evidence, and potential for past brucellosis identification and understanding, focussing on osteological markers in humans and animals, historical, biomolecular, and epidemiological approaches. We also present an agenda and potential for future research.